2021
DOI: 10.1016/j.waojou.2021.100611
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic features and burden of atopic dermatitis in adolescent and adult patients: A cross-sectional multicenter study

Abstract: Background: Atopic dermatitis (AD) is considered as one of the most frequent chronic skin conditions. Previous AD epidemiologic studies have been mainly retrospective and/or have been performed through surveys instead of in-person visits. Epidemiological studies concerning AD in Latin American countries are scarce.Objective: To describe sociodemographic and clinical features and the economic burden of AD on children and adult patients in Colombia through in-person visits.Methods: This was a cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Prevalence of atopic diseases varies between populations, for example, Sanclemente et al . reported in a comparable cross‐sectional study from Colombia a substantially lower prevalence in AD patients (chronic rhinitis 68.9%, allergic conjunctivitis 29.7%, asthma 28.8%) 39 …”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Prevalence of atopic diseases varies between populations, for example, Sanclemente et al . reported in a comparable cross‐sectional study from Colombia a substantially lower prevalence in AD patients (chronic rhinitis 68.9%, allergic conjunctivitis 29.7%, asthma 28.8%) 39 …”
Section: Discussionmentioning
confidence: 73%
“…38 Prevalence of atopic diseases varies between populations, for example, Sanclemente et al reported in a comparable cross-sectional study from Colombia a substantially lower prevalence in AD patients (chronic rhinitis 68.9%, allergic conjunctivitis 29.7%, asthma 28.8%). 39 There were more severe AD patients with hand dermatitis (82.1%), palmar hyperlinearity (41.8%) and contact allergies (25.7%), which seem to be linked to a more severe disease in Finnish patients. Palmar hyperlinearity has been linked to FLG mutations and possible markers of AD severity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a cohort of 1,650 Argentinian patients with AD, 40% experienced high itch intensity and frequency, and 96% reported bleeding and suppuration [24]. A cross-sectional study in Colombia found that disease distribution was mostly flexural and combined with either eyelid dermatitis, hand eczema, or cheilitis, and that most patients suffered from moderate disease when evaluated using body surface area (BSA) and eczema area and severity index (EASI) score [25]. In a recently published abstract, results from a study evaluating the burden of AD in Brazil, Mexico, and Argentina found that severe pruritus (Worst Pruritus NRS > 7) was reported by 54.4% of patients and with effect on the quality of life close to 50% of the 180 evaluated patients [26].…”
Section: Clinical Characteristics Impact On Quality Of Life and Ad As...mentioning
confidence: 99%
“…Over the past few decades, with the acceleration of industrialization, increase in environmental pollution, changes in lifestyle and dietary structure, and continuous increase in allergen exposure, allergy diseases affect 30–40% of the global population and cause a major disease burden worldwide [ 1 , 2 , 3 , 4 ], with an estimated 300 million patients with bronchial asthma (AS), 400 million patients with allergic rhinitis (AR), 200 million to 250 million patients with food allergy (FA), 150 million patients with drug allergy (DA), and numerous patients with allergic conjunctivitis (AC), angioneurotic edema, urticaria, eczema, eosinophilic diseases, insect allergy, and anaphylactic shock [ 5 ]. Concomitantly, allergy is listed by the World Health Organization (WHO) as one of the 6 major chronic diseases in the 21st century.…”
Section: Introductionmentioning
confidence: 99%